PENGEMBANGAN BAHAN AJAR TEKS ULASAN BERBANTUAN PIKTOCHART PADA SISWA KELAS VIII - Anella Roveriana Sitanggang; Khairil Ansari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the lack of varied teaching materials used in review text learning, which caused students’ interest and understanding to remain low. This study aimed to develop review text teaching materials assisted by the application Piktochart for eighth-grade junior high school students and to determine the feasibility level of the developed product. The research employed the Research and Development (R&D) method by adapting the simplified Borg and Gall model, which consisted of several stages, namely potential and problem analysis, data collection, product design, design validation, and product revision. Data collection techniques were conducted through observation, interviews, and questionnaires. The research instruments included validation sheets from material experts, media experts, and Indonesian language teachers. The results showed that the developed review text leaflet teaching materials assisted by Piktochart were categorized as highly feasible for use in the learning process, with an average assessment percentage of 92.61%. The developed product was arranged concisely, systematically, and attractively, and was adjusted to the Learning Outcomes (CP) of Phase D in the Merdeka Curriculum. Therefore, the Piktochart-assisted leaflet teaching materials are suitable for use as learning media to help improve students’ understanding and learning interest in review text materials.